Design of Guidance Law with Predefined Upper Bound of Settling Time - Kumar S.; Sharma R.K.; Kamal S. (My University, 2025)
The paper considers the design of guidance law with predefined upper bound of settling time for planar motion. The proposed scheme is based on a switched control action which results into a desired convergence of the line-of-sight (LOS) rate to zero or a small neighborhood of zero. With this technique, the convergence time of the LOS rate can be chosen as per will of the designer. This scheme considers both the cases where the target acceleration is known and when it is known with certain upper bound. Thus, the designed guidance law is applicable for both maneuvering and non-maneuvering targets. The sufficient condition for Lyapunov stability analysis is established for both the cases. The method is illustrated by considering a numerical example which shows the effectiveness of the proposed technique. © 2023 The Authors.